Financial Literacy and Financial Well-Being A Bibliometric Analysis - Heri Aryadi; Achmad Husen; Suparno Suparno (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study seeks to identify current research trends in Financial Literacy and Financial Well-Being, including the most cited studies, leading publishing countries, influential factors, research methodologies, and outcomes. A comprehensive review of the literature combined with bibliometric analysis utilizing VosViewer, examining 35 publications from the respected Scopus database over the past five years (2020-2024). Data analysis uses Vos Viewer to illustrate visualizations and networks for comprehending publication trends. The findings of this analysis indicate that India has the highest number of publications on this subject. The article by Philippas et al. has the greatest citation count, totaling 102 citations. The predominant approach is the quantitative method. Financial literacy pertains to a nexus of circumstances. The elements of capacity view and enhancing overall financials remain novel and have not been extensively studied. This research is anticipated to benefit policymakers, academics, researchers, and finance practitioners by improving their understanding of financial literacy and Financial well-being while suggesting relevant variables for future investigation.